Potential endocrine correlation with exposure to domoic acid in Southern Right Whale (Eubalaena australis) at the Península Valdés breeding ground - D'agostino, Valeria Carina; Fernández Ajó, Alejandro; Degrati, Mariana; Krock, Bernd; Hunt, Kathleen; Uhart, Marcela María; Buck, Charles Loren (Oecologia)
In waters off Península Valdés (PV), Argentina, southern right whales (SRW, Eubalaena australis) are occasionally exposed to domoic acid (DA), a neurotoxin produced by diatoms of the genus Pseudo-nitzschia. Domoic acid toxicity in marine mammals can cause gastrointestinal and neurological clinical signs, alterations in hematologic and endocrine variables, and can be fatal in extreme cases. In this study, we validated an enzyme immunoassay to quantify fecal glucocorticoid metabolites (fGCm) in sixteen SRW fecal samples from live and dead stranded whales in PV from 2013-2018 and assessed fGCm levels associated with DA exposure. Overall, fGCm levels were significantly lower in SRWs with detectable fecal DA (n=3) as compared to SRWs with undetectable fecal DA levels (n=13). The highest fecal DA was observed in a live lactating female, which had low fGCm compared to the other lactating females studied. The highest fGCm was observed in a lactating female with undetectable DA; interestingly, at the time of sample collection, this female was sighted with two calves, an extremely unusual occurrence in this species. Though sample size of these exceptionally rare breeding-season fecal samples was unavoidably small, our study provides evidence of potential adrenal alterations in whales exposed to an environmental neurotoxin such as DA. Fil: D'agostino, Valeria Carina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Fernández Ajó, Alejandro. State University of Oregon; Estados Unidos Fil: Degrati, Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Krock, Bernd. Alfred-Wegener-Institut, Helmholtz-Zentrum für Polar- und Meeresforschung; Alemania Fil: Hunt, Kathleen. George Mason University And Smithsonian; Estados Unidos Fil: Uhart, ...